Exercise restores impaired endothelium-derived hyperpolarizing factor–mediated vasodilation in aged rat aortic arteries via the TRPV4-KCa2.3 signaling complex - Huang J (Dove Medical Press, 2019)
Junhao Huang,1 Hai Zhang,2 Xianming Tan,1 Min Hu,1 Bing Shen31Guangdong Provincial Key Laboratory of Sports and Health Promotion, Scientific Research Center, Department of Sports and Health, Guangzhou Sport University, Guangzhou, Guangdong, People’s Republic of China; 2Department of Physical Education, Guangdong University of Petrochemical Technology, Maoming, Guangdong, People’s Republic of China; 3Department of Physiology, School of Basic Medical Sciences, Anhui Medical University, Hefei, Anhui, People’s Republic of ChinaCorrespondence: Min HuScientific Research Center, Guangzhou Sport University, 1268 Middle Guangzhou Avenue, Guangzhou 510500, People’s Republic of ChinaTel +86 0 203 802 7669Fax +86 0 203 802 7669Email whoomin@aliyun.comBing ShenDepartment of Physiology, Anhui Medical University, 81 Meishan Road, Hefei 230032, People’s Republic of ChinaTel +86 05 516 516 1132Fax +86 0 5516 516 1126Email shenbing@ahmu.edu.cnBackground: Aging leads to structural and functional changes in the vasculature characterized by arterial endothelial dysfunction and stiffening of large elastic arteries and is a predominant risk factor for cardiovascular disease, the leading cause of morbidity and mortality in modern societies. Although exercise reduces the risk of many age-related diseases, including cardiovascular disease, the mechanisms underlying the beneficial effects of exercise on age-related endothelial function fully elucidated.Purpose: The present study explored the effects of exercise on the impaired endothelium-derived hyperpolarizing factor (EDHF)–mediated vasodilation in aged arteries and on the involvement of the transient receptor potential vanilloid 4 (TRPV4) channel and the small-conductance calcium-activated potassium (KCa2.3) channel signaling in this process.Methods: Male Sprague-Dawley rats aged 19–21 months were randomly assigned to a sedentary group or to an exercise group. Two-month-old rats were used as young controls.Results: We found that TRPV4 and KCa2.3 isolated from primary cultured rat aortic endothelial cells pulled each other down in co-immunoprecipitation assays, indicating that the two channels could physically interact. Using ex vivo functional arterial tension assays, we found that EDHF-mediated relaxation induced by acetylcholine or by the TRPV4 activator GSK1016790A was markedly decreased in aged rats compared with that in young rats and was significantly inhibited by TRPV4 or KCa2.3 blockers in both young and aged rats. However, exercise restored both the age-related and the TRPV4-mediated and KCa2.3-mediated EDHF responses.Conclusion: These results suggest an important role for the TRPV4-KCa2.3 signaling undergirding the beneficial effect of exercise to ameliorate age-related arterial dysfunction.Keywords: endothelium, EDHF, exercise, TRPV4, KCa2.3, aging